Relationship With Stunting Learning Achievements Children Basic School Of State No. 07 Matajang - Tenriwati; Asri; Siti Nurindahyana (Jurnal Life Birth, 2019)
Lack of iron, folic acid, zinc, and others since the pregnancy of the mother can cause children born later to potentially experience stunting. Stunting can also affect a child's brain development because, since the fetus, the nutrients absorbed by the child for the development of its organs are lacking. If since the fetus has disturbed the child's brain it will be more difficult to fix it in the future. The purpose of this research analysis is to find out the relationship between stunting and children's learning achievement (grades 3 & 4) State Elementary School No. 07 Matajang Ujungbulu District Bulukumba Regency. The design of this study uses Analytic research with a Cross-Sectional suppressor. The population in this study were all students of Elementary School No. 07 Matajang totaling 128 people. The sampling technique uses a non-random sampling technique with the consecutive sampling method. The number of samples in this research were 54 respondents. Data analysis used the Kolmogorov-Smirnov alternative Chi-Square Test, with a significance level a = 0.05. The results of data analysis show that p = 0,000 <of a = 0.05 thus Ho is rejected and Ha is accepted, meaning that a meaningful result is obtained between stunting and children's learning achievement (grades 3 & 4) State Elementary School No. 07 Matajang Bulukumba Regency. Conclusion: There is a relationship between stunting and children's learning achievement (grades 3 & 4) Public Elementary School No. 07 Matajang Bulukumba Regency.